Exploring Social Assistance Policy's Role In Alleviating Poverty In Post-Apartheid South Africa - Ramushu, Tshidi (Department of Social Development, 2024)
Social assistance policy is an anti-poverty approach used by the South African government to tackle socio-economic challenges. This study analysed the social assistance policy's role in alleviating poverty in post-apartheid South Africa. Applying Sen's capability approach, the study explored the role played by the social assistance grants in alleviating poverty. Literature reviewed for the study revealed that social assistance as an anti-poverty measure has contributed significantly towards the reduction of poverty in post-apartheid South Africa. The results of this qualitative study show that the social assistance policy continues to play a critical role in significantly reducing the severity of poverty in Khayelitsha and Soweto, particularly in female-headed households. Grants reduce the economic and social vulnerability of poor households. The primary data was analysed using the thematic content analysis approach with the themes informed by both, interviews, and literature findings. Interviews with the participants who were accessed through purposive sampling revealed the provision of social grants play a significant role in relieving and uplifting many households from vulnerability, destitution, and poverty. Key indicators of this include: improved access to good nutrition, education, attainment of minimum standard of living, and access to the labour market